1993
DOI: 10.1002/jsfa.2740630210
|View full text |Cite
|
Sign up to set email alerts
|

Changes with maturity in fibre composition and levels of extractable polyphenols in Greek browse: Effects on in vitro gas production and in sacco dry matter degradation

Abstract: Neutral and acid detergent fibre (NDF, ADF), lignin, crude protein (CP), total extractable phenols (TEPH), tannins (TETa), condensed tannins (vanillin assay TECTa ; proanthocyanidins TEPAs) in the leaves of spring Phyllirea media (SPRG) or early summer (ESUM) and early autumn (EAUT) Carpinus duinensis, Quercus coccifera and Fraxinus ornus were studied. Gas production (in uitro) and dry matter (DM) degradation (in sacco) were also studied after incubation for up to 96 h. Concentrations of TEPH, TETa, TECTa, TEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
32
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 22 publications
9
32
0
2
Order By: Relevance
“…The results obtained in this experiment are in agreement with those reported by Khazaal et al (1993), Blummel and Orskov (1993) and Sileshi et al (1996), who observed a correlation between DM disappearance and gas production but they did not find a significant correlation between the rate of DM degradation (c is ) and the rate of gas production (c gas ). On the other hand, Piva et al (1988), who worked with maize silage, did not obtain a significant (P > 0.05) correlation for the same parameters.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in this experiment are in agreement with those reported by Khazaal et al (1993), Blummel and Orskov (1993) and Sileshi et al (1996), who observed a correlation between DM disappearance and gas production but they did not find a significant correlation between the rate of DM degradation (c is ) and the rate of gas production (c gas ). On the other hand, Piva et al (1988), who worked with maize silage, did not obtain a significant (P > 0.05) correlation for the same parameters.…”
supporting
confidence: 92%
“…Maize silage is the only forage containing starch in this experiment. Chemical compositions of forages used in this experiment were consistent with Khazaal et al (1993), Valentin et al (1999), Giger-Riverdin et al (2000).Cumulative gas production profiles from the in vitro fermentation of some forages are shown in Figure 1 and the estimated parameters are given Means within the same row with various superscripts are significantly different, c gas = gas production rate, a gas = gas production (ml) from quickly soluble fraction, b gas = gas production (ml) from insoluble fraction, (a + b) gas = potential gas production, ***P < 0.001, SEM = Standard Error Mean, Sig. = significance level…”
supporting
confidence: 71%
“…This is in agreement with Blümmel & Ørskov (1993), Khazaal et al (1993) and Sileshi et al (1996). The highly significant relationship between gas production and DM disappearance after 24 and 96 h incubation suggests that either method could be used to estimate the nutritive value of such tree leaves.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Menke et al (1979) and Menke & Steingass (1988) developed the in vitro gas production technique to evaluate the nutritive value of forages and estimate the rate and extent of DM degradation indirectly using the gas production (CO 2 ) during fermentation. The in situ nylon bag and in vitro gas production technique are well correlated with animal performance (Ørskov, 1989), food intake (Blummel & Ørskov, 1993), microbial protein synthesis (Krishnamoorthy et al, 1991) and in vivo digestibility (Khazaal et al, 1993). More recently researchers have been investigating the relationship between fermentation kinetics of forages obtained by the in situ nylon bag technique and the in vitro gas production technique (Blummel & Ørskov, 1993;Khazaal et al, 1993;Dewhurst et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Na avaliação de fatores anti-nutricionais através da produção de gases, nota-se que os efeitos destes fatores na fermentação do rúmen são refletidos pela queda da produção de gases (GETACHEW et al, 1998;SINGH;BHAT;SHARMA, 2001), podendo também interferir na determinação da digestibilidade in vitro (KHAZAAL et al, 1993;CABRAL FILHO et al, 2005 …”
Section: Produção De Gases In Vitrounclassified